Membangun Generasi Cerdas dari Desa Gunung Sari, Literasi Dasar Melalui Program Pembelajaran Interaktif - Grace Oktavia; Ifani Viola Risty Putri; Aleyda Nurvilaely; Zakia Sofi Salsa Bela Laili; Mutia Deshinta; Astrid Calista Saraswati Sejahtera; Muhammad Ikhwan Nugraha Putra; Agung Asmoro Aritonang; Moch Rizal Eka Ananda; Renaldy Rafi Arfansyah; Amongtyo Yuwono (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Gunungsari Village, Windusari District, is one of the areas facing quite serious challenges in efforts to develop basic literacy in school-age children. The main problems faced are low interest in reading, limited access to adequate reading materials, and learning methods that are still conventional. These conditions have implications for many children who are not able to read and write fluently despite having received an elementary school education. In response to this situation, the community service team took the initiative to implement a literacy program that uses an interactive learning approach through the development of a literacy park. This program is not only designed to be a learning platform, but also to create a learning atmosphere that is fun, contextual, and involves the active participation of children. Various activities are implemented, including storytelling, the provision of a reading corner, educational games such as math games, vocabulary quizzes, and the provision of simple rewards to maintain high learning motivation. This program activities are carried out periodically with the involvement of the school, the surrounding community, and also the village government, so that its sustainability has the support of various parties. The results of the implementation show a significant increase in children's literacy skills. Not only are they reading more fluently, but they are also better able to comprehend story content and write simple ideas. Furthermore, the children appear more confident in expressing themselves, are more active in every learning activity, and are beginning to demonstrate positive reading habits. A culture of literacy is also slowly growing through the existence of child-friendly and inclusive literacy parks. This proves that a fun, community-based literacy approach is highly relevant in rural areas with limited resources and can be a simple yet impactful means of educational transformation for children's futures.